2003
DOI: 10.1038/sj.cr.7290161
|View full text |Cite
|
Sign up to set email alerts
|

Expression and localization of VCX/Y proteins and their possible involvement in regulation of ribosome assembly during spermatogenesis

Abstract: Variable Charge X/Y (VCX/Y) is a human testis-specific gene family that localized on X and Y chromosomes. In this study, VCY protein was expressed in E. coli in the form of glutathione-S-transferase (GST) fusion protein. With the purified fusion protein as antigen, the anti-GST-VCY antibody was generated and the localization of VCY protein in human testis was determined by immunohistochemistry. In the testis seminiferous epithelium, VCY proteins were highly expressed in nuclei of germ cells. Using propidium io… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 13 publications
2
24
0
1
Order By: Relevance
“…To our knowledge, the relevance of VCX/Y to cancer has not been previously investigated. VCX/Y proteins are localized in the nucleus and may be involved in regulating ribosome assembly during spermatogenesis (32), inhibiting mRNA decapping and regulating mRNA stability (10). In our study, VCX siRNA inhibited cell proliferation in PC-9 cells, suggesting that VCX/Y genes have oncogenic roles.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, the relevance of VCX/Y to cancer has not been previously investigated. VCX/Y proteins are localized in the nucleus and may be involved in regulating ribosome assembly during spermatogenesis (32), inhibiting mRNA decapping and regulating mRNA stability (10). In our study, VCX siRNA inhibited cell proliferation in PC-9 cells, suggesting that VCX/Y genes have oncogenic roles.…”
Section: Discussionmentioning
confidence: 99%
“…VCX gene expression was reported to be restricted to the testis (Fukami et al, 2000; Lahn and Page, 2000; Zou et al, 2003). Nevertheless, we recently reported the cloning of the VCX-A gene product from human K562 erythroleukemia cells (Jiao et al, 2006), suggesting perhaps a preferential, rather than exclusive, expression in the testis.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, by RT-PCR, the Y chromosome localized VCY genes are exclusively and robustly expressed in male germ cells (Figure 1A). Despite the reported testis germ cell restriction of the VCX genes (Fukami et al, 2000; Lahn and Page, 2000; Zou et al, 2003), we initially cloned the cDNA of VCX-A from human K562 erythroleukemia cells (Jiao et al, 2006). The presence of the VCX-A mRNA in erythroleukemia cells indicated that expression of this gene is not restricted to testis.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, DAZ-family members have been shown to bind to specific transcripts in vivo and regulate pre-meiotic translation of important factors such as the mouse VASA-homolog MVH (Reynolds et al 2005), which in turn plays a major role in the processing of PIWI-interacting RNAs (Kuramochi-Miyagawa et al 2010). RNA binding has also been observed for the splicing-associated RBMY (Elliott et al 2000), while other genes residing within the AZFb locus exhibit transcription factor activity (HSFY; Tessari et al 2004) or are involved in ribosome assembly (VCY; Zou et al 2003). Hence, impairment of the testicular transcriptional network by altering the function of transcription factors through modulation of their mRNAs or their translation could play a putative role.…”
Section: Discussionmentioning
confidence: 99%